2013
DOI: 10.1111/clr.12264
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic restoration in the single‐tooth gap: patient preferences and analysis of the WTP index

Abstract: Within the limitations of this study, most of the population (64%) surveyed indicated the ISC as a therapeutic solution for the replacement of a single missing tooth, showing a higher WTP index in the anterior area. Among investigated socio-demographic variables, the importance assigned by the patient to oral care appeared to influence WTP values of the rehabilitation, regardless the location of the single gap in the mouth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 31 publications
3
26
1
Order By: Relevance
“…Despite very conservative stated treatment costs for implant care (€2000) both treatment groups indicated a median WTP value of only €1000 (p=0.511). This contrasts with previous WTP studies which indicate strong patient preferences for dental implants to replace missing teeth over treatment alternatives in Italy and Saudi Arabia 21,22 . However, the results mirror those found previously in Hong Kong where partially dentate patients recorded maximum WPT values of around half of the market price for implants to replace a missing tooth 20 .…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Despite very conservative stated treatment costs for implant care (€2000) both treatment groups indicated a median WTP value of only €1000 (p=0.511). This contrasts with previous WTP studies which indicate strong patient preferences for dental implants to replace missing teeth over treatment alternatives in Italy and Saudi Arabia 21,22 . However, the results mirror those found previously in Hong Kong where partially dentate patients recorded maximum WPT values of around half of the market price for implants to replace a missing tooth 20 .…”
Section: Discussioncontrasting
confidence: 82%
“…Influence of the level of income or the ability to pay on WTP seems to be a controversial topic in the current literature. Some researchers detected a positive association 12,21 , as in this study, whilst others found no influence 13,20 . It is somewhat surprising that gender did not influence WTP values recorded in this study as women tend to place a higher value on oral health and consume more oral health services.…”
Section: Discussionsupporting
confidence: 55%
“…Some studies discovered an interesting correlation between WTP and the presence or absence of esthetic considerations. Augusti et al [10] revealed that most patients with a missing tooth in the frontal part of their smile preferred an implant and were willing to pay a higher price for that. The farther back the missing tooth was located, the lower was the amount that patients were willing to pay.…”
Section: Discussionmentioning
confidence: 99%
“…Economic studies have shown that patients are willing to pay a large amount of money (from s1500 to s2500) for indirect restorative or implant-based closures of interdental spaces in the posterior region [2]. Here, direct composite buildups provide a "socially acceptable" treatment alternative that costs about s250 per tooth.…”
Section: Discussionmentioning
confidence: 99%
“…In special cases, orthodontic interventions, tooth transplantations or removable dentures can be considered as therapeutic options. Today, however, single missing teeth in the posterior region are mainly replaced by means of fixed dental prostheses of various kinds or single-tooth implants [2][3][4]. The most tooth saving option of an indirect restorative treatment in the posterior region are cantilever resin-bonded fixed partial dentures, that provide less biological damage and good esthetics [5].…”
Section: Introductionmentioning
confidence: 99%